Use of primary health care services and mortality in older patients with type 2 diabetes with or without comorbidities - E. Mellanen; T. Kauppila; H. Kautiainen; M. Lehto; O. Rahkonen; K. Pitkälä; M. K. Laine (Scandinavian Journal of Primary Health Care)
Objective This study aimed to examine primary health care (PHC) service utilization and mortality in older patients with type 2 diabetes (T2D) with or without comorbidities.Design and setting A cohort study in PHC in the city of Vantaa, Finland. Follow-up period was set between the years 2011 and 2018.Subjects PHC patients aged 60 years or more with a T2D were included.Main outcome measures Service utilization was defined as the number of face-to-face appointments and telephone contacts between a patient and general practitioner (GP) or nurse. The presence of comorbidities was defined using the Charlson Comorbidity Index (CCI). Mortality was assessed using hazard ratio (HR) and standardized mortality ratio (SMR).Results In total, 11,020 patients were included and followed for 71,596 person years. Mean age of the women and men in the beginning of follow-up were 71 and 69 years, respectively. The patients in the study cohort had a mean of eight appointments per person year to the GPs or nurses. Patients with T2D with comorbidities had more appointments than patients with T2D without comorbidities (incidence rate ratio (IRR) 1.44 [95% CI 1.39–1.49]). Increase in the number of all appointments reduced mortality in patients with T2D with and without comorbidities. Between patients with T2D with comorbidities and patients with T2D without comorbidities, the age and sex adjusted HR for death was 1.50 (95% CI 1.39–1.62). The SMR was higher in patients with T2D with comorbidities (1.83 [95% CI 1.74–1.92]) than in patients with T2D without comorbidities (0.91 [95% CI 0.86–0.96]).Conclusions In older patients with T2D, the presence of comorbidities was associated with increased use of PHC services and increased mortality. Increase in the number of appointments was associated with reduced mortality in patients with T2D with or without comorbidities.Key PointsIn older patients with T2D, it has not been studied whether and to what extend multimorbidity affects use of PHC services and mortality.The presence of comorbidities according to the Charlson Comorbidity Index (CCI) was associated with increased use of PHC services.The number of appointments to GPs or nurses was associated with reduced mortality in patients with T2D with or without comorbidities according to the CCI.